(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article reflects the analysis and conclusions on the systematization of thematic-linguistic units, which include realia in the German language and their classification features. In addition, the expediency of dividing thematic units and classifying real words from a semantic point of view is discussed in the classification of real words, distinguishing whether they are real or non-real words based on the context, and not translation